If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -8 = a + -4 Reorder the terms: -8 + 3a = a + -4 Reorder the terms: -8 + 3a = -4 + a Solving -8 + 3a = -4 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -8 + 3a + -1a = -4 + a + -1a Combine like terms: 3a + -1a = 2a -8 + 2a = -4 + a + -1a Combine like terms: a + -1a = 0 -8 + 2a = -4 + 0 -8 + 2a = -4 Add '8' to each side of the equation. -8 + 8 + 2a = -4 + 8 Combine like terms: -8 + 8 = 0 0 + 2a = -4 + 8 2a = -4 + 8 Combine like terms: -4 + 8 = 4 2a = 4 Divide each side by '2'. a = 2 Simplifying a = 2
| 10+2x-4=3x+2 | | 10x-124=97-3x | | 3/u=27/162 | | 2=-8y+2 | | 7.91=2 | | 16=7-3x | | 52=4v | | 3(3+4)=21 | | -13+2x+10=x+7 | | 7n-12=6 | | x+6/10+x-4/15=x+2/5 | | -3(a+2)-(a-6)=20 | | X-2/20=9/5 | | 3x^(4/3)+5x^(2/3)-2=0 | | b^2+8b-57=6 | | 1/-3=27 | | 7x+2=-9 | | 2w+6=52 | | 2x+22+14=14 | | 2x^2-4x=x^2+4x-1 | | 32/7+51/4-11/14 | | 7-7x+4x=-11 | | 3-1/5e=-7 | | U/-6+7=11 | | n+6=3n-10 | | y/4+2=c | | 3(x+4)=6+3x | | 27/10*10 | | x-8=r | | (8x^2+6x-5)-(6x^2+2)= | | 6x-32=3x+3 | | x-5=13-3x |